2019
DOI: 10.1038/s41598-019-48567-6
|View full text |Cite
|
Sign up to set email alerts
|

The Low Toxicity of Graphene Quantum Dots is Reflected by Marginal Gene Expression Changes of Primary Human Hematopoietic Stem Cells

Abstract: Graphene quantum dots (GQDs) are a promising next generation nanomaterial with manifold biomedical applications. For real world applications, comprehensive studies on their influence on the functionality of primary human cells are mandatory. Here, we report the effects of GQDs on the transcriptome of CD34 + hematopoietic stem cells after an incubation time of 36 hours. Of the 20 800 recorded gene expressions, only one, namely the selenoprotein W, 1, is changed by the GQDs in direct compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…Similar with graphene, GQDs have capability to bind with a variety of aromatic bimolecular through the π–π stacking interaction and/or electrostatic binding. However compared with graphene sheets, GQDs exhibit improved biocompatibility and minimal toxicity [ 16 18 ], making them more promising materials for delivering of biologically active cargoes into living systems. In recent years, many researchers have been dedicated to the application of GQDs in drug delivery systems [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar with graphene, GQDs have capability to bind with a variety of aromatic bimolecular through the π–π stacking interaction and/or electrostatic binding. However compared with graphene sheets, GQDs exhibit improved biocompatibility and minimal toxicity [ 16 18 ], making them more promising materials for delivering of biologically active cargoes into living systems. In recent years, many researchers have been dedicated to the application of GQDs in drug delivery systems [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A smaller uptake avidity of CD3 + T and T helper cells compared to CD19 + B cells from healthy donors was already observed in our previous study. 19 The difference between these two types of lymphoid cells may relate to the phagocytic ability of activated B cells. 39 The t-SNE plots (Fig.…”
Section: Cellular Uptake Of Cndsmentioning
confidence: 99%
“…Based on the results of previous studies in HSCs and human breast cancer cells using a counterstaining method these clusters could be localized to lysosomes. 19,40 It is therefore conceivable that the CNDs following ingestion into the leukemic blasts are stored in the lysosomes, suggesting that the endolysosomal pathway is also effective in AML cells. In the light of this nding the results of Folkerts et al are interesting and of potential therapeutic relevance.…”
Section: Subcellular Distribution Of Cnds In Aml Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The desirable biocompatibility was related with the small sizes and ease of clearance from their body and high oxygen content [ 106 ]. In a very recent study, it was demonstrated that GQDs can alter one gene’s expression on CD 34+ hematopoietic stem cells after 36 hours of incubation, which is a negligible number within 20,800 genes [ 107 ].…”
Section: Introductionmentioning
confidence: 99%